OBTAINING AND CHARACTERIZATION OF NANOCOMPOSITE: SILVER NANOPARTICLES AND CARBOXIMETHYLQUITOSAN (NPsAg-CMQ) - Zea Álvarez, Julia Lilians (2019)
The synthesis of the nanocomposite based on silver nanoparticles and O-carboxymethyl chitosan (NPsAg-CMQ), by the chemical reduction method, using the O-carboxymethylchitosan 0.01% and AgNO3 1 mM in a ratio of 3: 2, with a time of 30 minute reaction, at room temperature and neutral pH. The nanocomposite obtained from the complex [Ag(NH3)2]+ was synthesized under the same conditions as AgNO3 but at a basic pH. Using UV-VIS spectrophotometry, the plasmon formation of silver nanoparticles at 410nm was verified for both silver sources. The results by Dynamic Light Dispersion (DLS) for AgNO3, shows a monodisperse distribution of the nanocomposite with an average hydrodynamic size of 166.7 nm. In the case of the diamine silver [Ag(NH3)2] + 83.9% had an average size of 54.42 nm. and 15.2% of 4.48 nm. Infrared Spectroscopy Measurements with Fourier Transform (FT-IR) shows the inhibition of the spectral bands at 879 and 723 cm-1 indicating the presence of NPsAg in the nanocomposite NPsAg-CMQ. The results of scanning electron microscopy (SEM-STEM) showed that the silver nanoparticles in the nanocomposite were spherical in shape and of a size of 5 to 20 nm.